2017
DOI: 10.1038/s41598-017-01540-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk of death from cardiovascular disease following breast cancer in Southeast Asia: a prospective cohort study

Abstract: Breast cancer incidence and survival is high in Southeast Asia. As such, many women diagnosed with breast cancer are at risk of dying of other causes. Given the increased risk of cardiotoxicity induced by breast cancer treatments, it is important to identify patients at high risk of cardiovascular disease (CVD) mortality. The aim of this study was to investigate if this risk varies by age and ethnicity. Patient details were obtained from 5,868 Chinese, Malay, and Indian women diagnosed with in situ or non-meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Cardiovascular disease (CVD) was the leading cause of death worldwide from 2006 through 2016, and several studies have assessed CVD mortality in cancer survivors . However, studies of mortality from other noncancer events are outdated or only report on deaths from specific causes, such as suicide and respiratory disease .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular disease (CVD) was the leading cause of death worldwide from 2006 through 2016, and several studies have assessed CVD mortality in cancer survivors . However, studies of mortality from other noncancer events are outdated or only report on deaths from specific causes, such as suicide and respiratory disease .…”
Section: Introductionmentioning
confidence: 99%
“…11 Cardiovascular disease (CVD) was the leading cause of death worldwide from 2006 through 2016, 12 and several studies have assessed CVD mortality in cancer survivors. [13][14][15][16][17] However, studies of mortality from other noncancer events are outdated 9 or only report on deaths from specific causes, such as suicide 14,15 and respiratory disease. 7,17 To the best of our knowledge, only 1 recent study from the United States reported the risk of death from specific noncancer events among patients with all cancers combined.…”
Section: Introductionmentioning
confidence: 99%
“…9 , 10 , 11 Although the Japan Breast Cancer Research Group (JBCRG) reported that the 3‐year cumulative incidence of trastuzumab‐related cardiotoxicity was only 0.54% among 2024 patients, in other single‐centre studies in Saudi Arabia, Singapore and China, 17 showed that the overall percentages of LVEF reduction ranged from 11.2 to 39.1%. 4 , 23 , 24 However, most of these studies had small sample sizes and lacked comparison groups. Notably, although a relative large portion of patents included in this study were premenopause and free from traditional cardiovascular risk factors, the incidence of trastuzumab‐related cardiotoxicity was not significantly different from that in the Western countries.…”
Section: Resultsmentioning
confidence: 99%
“…The 5-year survival rate for breast cancer has significantly increased over the last two to three decades in multiple countries including Korea , studies reveal that breast cancer survivors who received anthracycline-based chemotherapy have been identified with heart disease, referred to as cardiomyopathy, up to 4 to 20 years after the completion of chemotherapy 6,7 , contributing to a higher risk for cardiovascular disease (CVD) compared to non-cancer controls [8][9][10] . These disadvantageous elements can be furthered supplemented by the fact that adverse effects caused by cancer therapies, accompanied by preexisting comorbidities such as obesity 11 , hypertension 12 , and type 2 diabetes 13 , increase the risk of developing CVD in breast cancer survivors as well 14,15 .…”
Section: Introductionmentioning
confidence: 99%